Human face a journalist's encounters and awakenings : selected columns from the Philippine Daily Inquirer - Doyo, Ma. Ceres P. (Mandaluyong City Makati City Anvil Publishing, Inc. Inquirer Books, 2013)
Essays on experiences of a journalist.
In English.
Keywords: Doyo, Ma. Ceres P; Journalists -- Philippines -- Biography; Newspapers -- Sections, columns, etc; Journalism -- Sources. -- Philippines -- History